2012
DOI: 10.1002/adma.201202722
|View full text |Cite
|
Sign up to set email alerts
|

Light Induced Nanowire Assembly: The Electrostatic Alignment of Semiconductor Nanowires into Functional Macroscopic Yarns

Abstract: The electrostatic alignment and directed assembly of semiconductor nanowires into macroscopic, centimeter-long yarns is demonstrated. Different morphologies can be produced, including longitudinally segmented/graded yarns or mixed composition fibers. Nanowire yarns display long range photoconductivities and open up exciting opportunities for potential use in future nanowire-based textiles or in solar photovoltaics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…Resulting diameters were on the order of *10-40 nm with lengths on the micrometer scale. Finally, Petchsang et al demonstrated the growth of ZnSe NWs using Zn(stearate) 2 , TOPSe and BiCl 3 in tri-n-octylphosphine oxide (TOPO) [37]. The mean NW diameter was *22 nm with lengths on the order of 10 μm.…”
Section: Synthesis Of Group Ii-vi Nwsmentioning
confidence: 96%
See 4 more Smart Citations
“…Resulting diameters were on the order of *10-40 nm with lengths on the micrometer scale. Finally, Petchsang et al demonstrated the growth of ZnSe NWs using Zn(stearate) 2 , TOPSe and BiCl 3 in tri-n-octylphosphine oxide (TOPO) [37]. The mean NW diameter was *22 nm with lengths on the order of 10 μm.…”
Section: Synthesis Of Group Ii-vi Nwsmentioning
confidence: 96%
“…This was followed by the work of Dong et al who produced ZnSe x Te 1−x NWs using Bi NPs in the presence of Zn(stearate) 2 and trioctylphosphine selenide (TOPSe)/TBPTe [35]. Resulting diameters were on the order of 10 nm with accompanying lengths of *1 μm.…”
Section: Synthesis Of Group Ii-vi Nwsmentioning
confidence: 97%
See 3 more Smart Citations